EMOTIONAL LABOUR: AN ARCHETYPAL ELEMENT OF HOSPITALITY SERVICE – A REVIEW - Sanjay Bhattacharya; Hirak Dasgupta (ASEAN Journal on Hospitality and Tourism, 2018)
Abstract. Emotional labour – the act of subduing one’s felt emotions in order to display organisationally accepted emotions at work, is entwined with hospitality service since time immemorial. It has its commercial value and hence is regularly exchanged for pay. Emotional labour has its antecedents and eventual consequences on the employees performing it. There are various ways through which hospitality service employees perform emotional labour on a daily basis. The social construct of hospitality, both cultural and religious, have augmented the necessity of emotional labour in delivery of service to the guest. Thereby, making it a standard element of the overall hospitality experience paradigm. A lot of research has gone into understanding the cause and effect relationship of the ‘antecedent-consequence’ framework of emotional labour. This paper delves into the existing literature surrounding emotional labour. Interestingly, it was found that a deeper insight about the phenomenon of emotional labour and its lived experience by the individual employee still awaits its due attention.